Prospects for Improving Nutrition in Eastern Europe and Central Asia - Rokx, Claudia (Washington, DC: World Bank, 2013)
Under-nutrition, and micronutrient deficiencies are critical issues for Eastern Europe and Central Asia. Failure to target programs to address the impact of malnutrition, has led to high rates of under-nutrition, and iron and iodine deficiencies. This report highlights the life-threatening nutrition problems confronting people in the region, and suggests strategies for change: a) improving infant feeding, particularly in Central Asia, to reduce unacceptably high rates of under-nutrition in young children; b) increasing consumption of iodized salt, to reduce compromised intelligence levels; and, c) developing programs to reduce iron deficiency anemia in women, and young children. Policymakers, and healthcare providers must develop, and deliver consistent, persuasive messages. This book aims to help raise awareness of nutrition problems in the region, and, suggests solutions for reducing malnutrition.